Investigations of MWISP Filaments. I. Filament Identification and Analysis Algorithms, and Source Catalog - Yu Jiang; Xuepeng Chen; Sheng Zheng; Zhibo Jiang; Zhiwei Chen; Yao Huang; Yang Su; Li Sun; Jian-Cheng Feng; Haoran Feng; Ji Yang (The Astrophysical Journal Supplement Series)
Filaments play a crucial role in providing the necessary environmental conditions for star formation, actively participating in the process. To facilitate the identification and analysis of filaments, we introduce Directional and Positional Consistency between Clumps and Filaments (DPConCFil), a suite of algorithms comprising one identification method and two analysis methods. The first method, the consistency-based identification approach, uses directional and positional consistency among neighboring clumps and local filament axes to identify filaments in the position–position–velocity data cube. The second method employs a graph-based skeletonization technique to extract the filament intensity skeletons. The third method, a graph-based substructuring approach, allows the decomposition of complex filaments into simpler subfilaments. We demonstrate the effectiveness of DPConCFil by applying the identification method to the clumps detected in the Milky Way Imaging Scroll Painting survey data set by FacetClumps, successfully identifying a batch of filaments across various scales within 10° ≤ l ≤ 20°, −5 $\mathop{.}\limits^{° }$ 25​​​​​​ ≤ b ≤ 5 $\mathop{.}\limits^{° }$ 25, and −200 km s ^−1 ≤ v ≤ 200 km s ^−1 . Subsequently, we apply the analysis methods to the identified filaments, presenting a catalog with basic parameters and conducting statistics of their galactic distribution and properties. DPConCFil is openly available on GitHub ( https://github.com/JiangYuTS/DPConCFil ), accompanied by a manual.